Strong macrobenthic community differentiation among sub-Arctic deep fjords on small spatial scales. (5th May 2021) - Kokarev, Valentin; Tachon, Mathieu; Austad, Marthe; McGovern, Maeve; Reiss, Henning
Abstract: Fjords play an important role in carbon cycling and sequestration, but the burial of organic matter in sediments strongly depends on the composition of macrobenthic communities. We studied three deep, sub-Arctic fjords located in northern Norway to assess the community differentiation of neighbouring fjords and the underlying environmental drivers. The fjords have relatively deep depositional basins (370–570 m), but they differ in sill depth and water exchange. In all fjords studied, the silty sediments were characterised by organic matter of mostly marine origin. We found that each basin was inhabited by a distinct benthic community, with pronounced differences in total abundance, biomass and species diversity. Only in one fjord (Skjerstadfjord), with a shallow sill, a slight mouth-to-head pattern of the community was found. The strong differentiation of macrobenthos among different fjords seems not to be directly associated with environmental drivers such as organic matter input, water masses or depth. Highlights: Three sub-Arctic fjords with deep basins (>350 m) were studied. Each basin was inhabited by a distinct macrobenthic community. Within-fjord variation was little and mainly related to organic matter supply. Sill depth affected water exchange and macrofaunal composition. Stochastic processes are proposed as a driver for among-fjord variation.